A Critical Blimp-1-Dependent IL-10 Regulatory Pathway in T Cells Protects From a Lethal Pro-inflammatory Cytokine Storm During Acute Experimental Trypanosoma brucei Infection - De Trez, Carl; Stijlemans, Benoit; Bockstal, Viki; Cnops, Jennifer; Korf, Hannelie; Van Snick, Jacques; Caljon, Guy; Muraille, Eric; Humphreys, Ian R.; Boon, Louis; Van Ginderachter, Jo A.; Magez, Stefan (Frontiers in Immunology, 2020)
In many infectious diseases, the immune response operates as a double-edged sword. While required for protective immunity, infection-induced inflammation can be detrimental if it is not properly controlled, causing collateral body damage and potentially leading to death. It is in this context that the potent anti-inflammatory cytokine interleukin-10 (IL-10) is required to dampen the pro-inflammatory immune response that hallmarks trypanosomosis. Effective control of this infection requires not just the action of antibodies specific for the parasite’s variable surface glycoprotein (VSG) coat antigens, but also a pro-inflammatory immune response mediated mainly by IFNγ, TNF and NO. However, strict control of inflammation is mandatory, as IL-10-deficient mice succumb from an unrestrained cytokine storm within 10 days of a Trypanosome brucei infection. The relevant cellular source of IL-10 and the associated molecular mechanisms implicated in its trypanosomosis associated production are poorly understood. Using an IL-10 reporter mouse strain (Vert-X), we demonstrate here that NK cells, CD8+ T cells and CD4+ T cells are the predominant sequential cellular sources of IL-10 within the spleen and liver during acute infection. The IL-10 wave follows peak pro-inflammatory cytokine production, which accompanied the control of peak parasitemia. Similar results were observed following conventional experimental needle infection and physiological infections via T. brucei-infected tsetse flies. Our results show that conditional T cell-specific ablation of the IL-10 regulating Prdm1 gene (encoding for the Blimp-1 transcription factor), leads to an uncontrolled trypanosome-induced pro-inflammatory syndrome like the one observed in infected IL-10-deficient mice. This result indicates that the biological role of IL-10-derived from non-T cells, including NK cells, is of minor importance when considering host survival. The cytokine IL-27 that is also considered to be an IL-10 regulator, did not affect IL-10 production during infection. Together, these data suggest that T. brucei activates a Blimp-1-dependent IL-10 regulatory pathway in T cells that acts as a critical anti-inflammatory rheostat, mandatory for host survival during the acute phase of parasitemia.